Inflammation Is Present, Persistent and More Sensitive to Proinflammatory Triggers in Celiac Disease Enterocytes - Porpora, Monia (2022)
Celiac disease (CD) is a chronic inflammatory disease caused by a genetic predisposition to an abnormal T cell-mediated immune response to the gluten in the diet. Different environmental proinflammatory factors can influence and amplify the T cell-mediated response to gluten. The aim of this manuscript was to study the role of enterocytes in CD intestinal inflammation and their response to different proinflammatory factors, such as gliadin and viruses. Intestinal biopsies from CD patients on a gluten-containing (GCD-CD) or a gluten-free diet (GFD-CD) as well as biopsies from potential CD patients (Pot-CD) before the onset of intestinal lesions and controls (CTR) were used to investigate IL-1β and IL-6 mRNA levels in situ. Organoids from CD patients were used to test the levels of NF-κB, ERK, IL-6, and IL-1β by Western blot (WB), ELISA, and quantitative PCR. The Toll-like receptor ligand loxoribine (Lox) and gliadin peptide P31-43 were used as proinflammatory stimuli. In CD biopsies inflammation markers IL-1β and IL-6 were increased in the enterocytes, and also in Pot-CD before the onset of the intestinal lesion and in GFD-CD. The inflammatory markers pNF-κB, pERK, IL-1β, and IL-6 were increased and persistent in CD organoids; these organoids were more sensitive to P31-43 and Lox stimuli compared with CTR organoids. Taken together, these observations point to constitutive inflammation in CD enterocytes, which are more sensitive to inflammatory stimuli such as food components and viruses.